The progression rate of aortic stenosis: key to tailoring the management and potential target for treatment. Issue 11 (29th November 2021) - Tafciu, Elvin; Mandoli, Giulia E.; Santoro, Ciro; Setti, Martina; d'Andrea, Antonello; Esposito, Roberta; Bandera, Francesco; Evola, Vincenzo; Malagoli, Alessandro; Cameli, Matteo; Benfari, Giovanni
Abstract : Aortic stenosis is the most frequent valvular disease to require intervention in the western world and has always been featured as a progressive disease. The rate of progression can be assessed by carefully performed Doppler echocardiography and can vary greatly between individuals with a profound impact on prognosis. Unfortunately, the determinants of disease progression had been insufficiently studied and remain challenging to define, particularly in the outpatient setting. Multiple factors have been proposed and tested, but at present, there are no proven therapies to slow the course of the stenotic process. Heart valve clinics may be particularly important to define the progression rate and tailor follow-up and management at an individual level. This review enlightens knowledge and gaps regarding the progression-rate of aortic valve stenosis, from the historical perspective to the molecular one.